2020
DOI: 10.21203/rs.2.22029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poverty reduces maternity waiting home utilization in Sidama Zone, southern Ethiopia

Abstract: Background : Maternity waiting home utilization is proved to decrease maternal mortality and morbidity. Maternity waiting home service utilization is a strategy to improve facility-based skilled delivery service in Ethiopia. Though the establishment of maternity waiting homes started in Ethiopia more than three decades back, the utilization of the service seems to low. The objective of this study is to estimate the magnitude of maternity waiting home utilization and identify its associated factors in Sidama Zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…To improve the current uptake of existing MWH facilities, issues that may negatively affect women's ability to use MWHs need to be addressed; in particular, greater awareness should be created about the facilities and attention should also be paid to their physical condition and the quality of care they provide [57]. Other studies have also suggested that some interventions like providing the women with food and basic supplies for the duration of their stay while ensuring basic sanitation would significantly improve the uptake of existing MWH services [34]. Besides, fostering a sense of communal ownership, improving women's education, and promoting the importance of MWHs among health care providers and community leaders may have a significant impact on the sustainability of the service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the current uptake of existing MWH facilities, issues that may negatively affect women's ability to use MWHs need to be addressed; in particular, greater awareness should be created about the facilities and attention should also be paid to their physical condition and the quality of care they provide [57]. Other studies have also suggested that some interventions like providing the women with food and basic supplies for the duration of their stay while ensuring basic sanitation would significantly improve the uptake of existing MWH services [34]. Besides, fostering a sense of communal ownership, improving women's education, and promoting the importance of MWHs among health care providers and community leaders may have a significant impact on the sustainability of the service.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of MWHs as a crucial link for other maternal health services, as well as their availability as a way to overcome the geographic gap in access to healthcare facilities, were identified as typical enablers in the literature. Women staying at MWH have the opportunity to share experiences with other pregnant mothers, postpartum health education about family planning, infant feeding, and connecting women to the health facility and PNC services for both mothers and newborns [34].…”
Section: Availability Of Mwhsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be also explained because the health services delivery system and a health care system to improve the survival of preterm neonates is limited in the setting 77 including poor uptake of maternity waiting home in the health facility. [78][79][80] Since a systematic review and meta-analysis were done in Africa revealed that maternity waiting for home utilization significantly reduced the risk of perinatal mortality. 81,82 This study found that a significant higher odd of stillbirth among preterm babies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Different primary studies were conducted in Ethiopia and estimated the prevalence of maternity-waiting home utilisation. [13][14][15][16][17][18][19][20][21][22][23][24] According to these separate studies, the prevalence of maternity-waiting home use among Ethiopian women ranges from 7% 16 to 68.8%, 17 and there was a significant variation and inconsistency in the prevalence of maternity-waiting home use among women across the country. Similarly, the factors associated with the utilisation of MWHs were different from study to study.…”
Section: Introductionmentioning
confidence: 99%